2017
DOI: 10.1364/boe.8.005087
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optics stochastic optical reconstruction microscopy (AO-STORM) by particle swarm optimization

Abstract: Stochastic optical reconstruction microscopy (STORM) can achieve resolutions of better than 20nm imaging single fluorescently labeled cells. However, when optical aberrations induced by larger biological samples degrade the point spread function (PSF), the localization accuracy and number of localizations are both reduced, destroying the resolution of STORM. Adaptive optics (AO) can be used to correct the wavefront, restoring the high resolution of STORM. A challenge for AO-STORM microscopy is the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…To analyze the mitochondrial network organization, we developed an angular Fourier filtering (AFF) method, based on a Fourier metric previously used for sensorless Adaptive Optics (70). Transforming an image from the spatial domain ( fig.…”
Section: -Photon Scanning Microscopymentioning
confidence: 99%
“…To analyze the mitochondrial network organization, we developed an angular Fourier filtering (AFF) method, based on a Fourier metric previously used for sensorless Adaptive Optics (70). Transforming an image from the spatial domain ( fig.…”
Section: -Photon Scanning Microscopymentioning
confidence: 99%
“…where their movement is affected by the individually best solution it found so far, as well as the groups best solution. Particle-swarm optimization was implemented via MATLAB particleswarm with a swarm size of 25 as suggested [8] with a maximum of 20 iterations for a maximum of 300 acquisitions. We used an initial swarm spansize of 0.1 rad and a maximum spansize of 0.75 rad.…”
Section: Particle-swarm Optimization Uses a Collection Of Solutions Mmentioning
confidence: 99%
“…WS technology has previously shown that 2-photon imaging through intact skull of juvenile mouse skull is possible [19]. By engineering the wavefront and restoring the diffraction-limited PSF, WS can correct for low and high order aberrations, and enhance both the peak and width of the PSF deep inside of a sample [4,[20][21][22][23][24][25][26][27][28][29][30], which has many applications in the musculoskeletal system [31] and nervous system [32] imaging.…”
Section: Introductionmentioning
confidence: 99%